Analysis of Determinants of Persuasive Communication Between Resellers and Consumers of the Make Over Brand - Nurhadiah; Isnaini Harahap; Siti Aisyah (Jurnal Ad'ministrare: Jurnal Pemikirian Ilmiah dan Pendidikan Administrasi Perkantoran, 2024)
The purpose of this research is to analyze the key determinants of persuasive communication strategies employed by resellers to enhance product sales and brand awareness of the Make Over brand in Medan City. This qualitative study adopts a descriptive approach, collecting data through interviews and documentation involving three key informants from May to September 2024. The findings reveal that effective persuasive communication is achieved through a strong connection between resellers and the brand, an understanding of consumer motivations, and strategic communication methods. Resellers utilize a mix of emotional and rational appeals, tailoring their messages to meet consumer needs. Face-to-face interactions play a vital role in building trust and credibility, while a combination of online and offline channels, including consumer testimonials, strengthens their marketing efforts. This study’s novelty lies in exploring how resellers leverage persuasive communication strategies to boost sales and elevate brand presence, specifically in the context of the Make Over brand in Medan City.